Cloud IaaS Enterprise Architecture Design on Multiplatform Integrated Information System using Cloud Ecosystem Reference Model and TOGAF - Setiyo Widayat; M Suksrisno Mardiyanto (LPPM ITK, 2018)
Currently Information Technology is increasingly needed by many organizations. Implementation of inappropriate IT in the organization will be a burden, even can hinder the development if not in accordance with the vision and mission of the organization. Weill and Ross also stated, 48 percent of companies that do IT investment cannot increase the expected value. A solid foundation in the execution process of IT implementation plays an important role in determining the success or failure of the company to achieve the desired goals. To build a solid foundation on the execution process of IT implementation, one of the important things to note is Enterprise Architecture (AE). Enterprise architecture provides a long-term view of the processes, systems and technologies in the company, so there is a harmony between business and IT both for now and for the future to achieve the desired goals. Currently the use of cloud computing technology increasingly used in organizations. Organizations typically have a variety of different platform integrated applications that are used to support their business processes. There are many frameworks used to build AE, but there is no AE framework specifically addressing AE design on cloud computing and supports multiplatform and cloud-based IaaS. This paper discusses the use of TOGAF and CERM to educational institution that have many integrated multiplatform applications. AE design that was built is validated by using Enterprise Realization Score Card (EARS) to assess whether it can be implemented well in the organization.